Pemetaan Potensi Ekonomi Wilayah Di Kalimantan Tengah Menggunakan Integrasi Analisis Klaster Hirarki, Shift-Share, Dan Location Quotient Dinamis - Herry Kristedy; Alexandra Hukom (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to map the economic potential in the Central Kalimantan region using the integration of three analytical methods, namely Hierarchical Cluster Analysis, Shift-Share, and Dynamic Location Quotient. Through this approach, this research identifies economic sectors that have comparative and competitive advantages at the local level and have the potential for further development. Hierarchical Cluster Analysis is used to group regions based on similar economic characteristics, while Shift-Share Analysis helps in determining sectors that contribute to regional economic growth. Dynamic Location Quotient is applied to assess changes in the comparative advantage of economic sectors over time. It is hoped that the results of this research can become a reference for stakeholders in formulating appropriate regional economic policies to encourage sustainable economic growth in Central Kalimantan.